1972
DOI: 10.1029/jb077i002p00351
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characteristics and stress drop for microearthquakes near Fairview Peak, Nevada

Abstract: Frequency and amplitude characteristics were studoeed for microearthquakes recorded on a local network of vertical-component seismographs in the Fairview Peak area of central Nevada. Maximum trace amplitude o.f the events decreased with focal distance approximately as R -•'9. Site amplification, by a factor of 2, was observed for the only station not located on rock. Comparison of observed spectra for these events with theoretical spectra given by Brune indicates stress drops ranging from 0.04 to 0.60 bar. Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Many studies have, however, used these theoretical models, especially that of Brune (1970), to get estimates of source parameters for local earthquakes (e.g. Douglas & Ryall 1972;Thatcher & Hanks 1973;Hartzell & Brune 1977, Brune, Archuleta & Hartzell 1979Bungum, Vaage & Husebye 1982;Kulhanek et al 1983;Scherbaum & Kisslinger 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have, however, used these theoretical models, especially that of Brune (1970), to get estimates of source parameters for local earthquakes (e.g. Douglas & Ryall 1972;Thatcher & Hanks 1973;Hartzell & Brune 1977, Brune, Archuleta & Hartzell 1979Bungum, Vaage & Husebye 1982;Kulhanek et al 1983;Scherbaum & Kisslinger 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Y1, Y2 and Y3 are local co-ordinates and X1, X2 and X3 are global co-ordinates. addition to micro-earthquakes(Douglas and Ryall 1972;Kumar et al 2006) thus covering a very wide range of computed values for source parameters based on the theory.…”
mentioning
confidence: 99%
“…Douglas ~~, (1970) and Douglas and Ryall (1972) have studied Basin and Range events and concluded that scaling laws accepted for large events seem to apply for earthquakes as small as magnitude 1. To allow comparison with other central California areas, Brune's (1970) widely used source model for S-waves, extended to P-waves, was applied.…”
Section: Attenuationmentioning
confidence: 99%